APEC 2015: Global Value Chains and Services - Ramonette B. Serafica (Philippine Institute for Development Studies (PIDS), 2015)
APEC 2015 provides an opportunity for the Philippines to advance its economic interests in services and contribute to regional integration by focusing on global value chains (GVCs) that are now believed to account for more than 50 percent of global trade. This paper looks at the GVC phenomenon and presents measures of GVC participation at the aggregate level. It then discusses the role of services in GVCs and proposes that further analytical work on services value chains in the Asia-Pacific region be undertaken. This will contribute to a better understanding of how individual economies can maximize GVC participation and how APEC can create the appropriate policy environment conducive to the growth of services value chains.
Keywords: 330; global value chains; APEC Philippine hosting; APEC services; competitive services